2001
DOI: 10.1046/j.1537-2995.2001.41121601.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the intensity of serial automated plasmapheresis and the speed of deep‐freezing on the quality of plasma

Abstract: Source plasma collected from donors undergoing intensified plasmapheresis contains markedly lower levels of IgG than plasma units produced by moderate serial plasmapheresis. The combination of intensified plasmapheresis and slower freezing of source plasma results in substantially lower levels of FV and FVIII than does moderate plasmapheresis with rapid freezing. Prospective studies should establish the optimum conditions required for the safe and economic production of source plasma for fractionation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 16 publications
1
20
1
1
Order By: Relevance
“…However, it was not our intention to include a study group donating according to US guidelines, because we felt that the conditions of plasma donation in our three study groups would guarantee a high‐quality source of plasma, in addition to high donor safety. A recent study reported that US source plasma contained lower TSP, albumin, IgG and factor VIII concentrations than plasma collected according to the GG [23]. Finally, despite relatively large sample sizes, our study may have overlooked minor variations between groups as a result of the high biological variability of some parameters, resulting in insufficient statistical power.…”
Section: Discussionmentioning
confidence: 88%
“…However, it was not our intention to include a study group donating according to US guidelines, because we felt that the conditions of plasma donation in our three study groups would guarantee a high‐quality source of plasma, in addition to high donor safety. A recent study reported that US source plasma contained lower TSP, albumin, IgG and factor VIII concentrations than plasma collected according to the GG [23]. Finally, despite relatively large sample sizes, our study may have overlooked minor variations between groups as a result of the high biological variability of some parameters, resulting in insufficient statistical power.…”
Section: Discussionmentioning
confidence: 88%
“…Studies dealing with the composition of non–pathogen‐reduced, WB‐derived plasma preparations for transfusion have neglected the influence on quality of the conditions under which the plasma was frozen. Three studies have shown that the amount of FVIII recovered in plasma depends on the velocity and the temperature of plasma freezing . Source plasma units frozen completely within 1 hour to a core temperature below −30°C contained significantly greater levels of FV and FVIII than plasma units frozen more slowly at −30°C in large walk‐in freezers, which takes several hours to reach a core temperature of −30°C .…”
Section: Discussionmentioning
confidence: 99%
“…Some authors state that freezing was performed at −20 °C, −30 °C, −40 °C, −60 °C, −70 °C and −80 °C but do not describe the shape or size of the containers used. If only the freezing temperature is defined it is impossible to calculate the actual freezing rate or the ice front velocity [4–6,13,15].…”
Section: Discussionmentioning
confidence: 99%